181 Epidemiology of ambulance attended falls in adults in WA 2015–2020. (20th November 2022) - Watkins, Paige; Finn, Judith; Hill, Anne-Marie; Brink, Deon; Tohira, Hideo; Buzzacott, Peter
Abstract : Background: Western Australia's (WA) ageing population is resulting in increased demand for emergency ambulance attendances to falls. Methods: The electronic patient care records of adult patients (>18 yrs.) who fell and required St John WA ambulance attendance between 1st Jan 2015 – 31st Dec 2020 were analysed. Results: 157, 280 patients (female = 90, 090, 57%) were attended by ambulances after falls, 116, 801 (74%) within Perth metro region and 40, 298 (26%) in rural WA (2015: 22, 567; 2016: 24, 116; 2017: 25, 407; 2018: 26, 833; 2019: 29, 031; 2020: 29, 326). Median age was 80 years [IQR 67–87]. 74, 015 (47%) patients sustained a reported injury, most commonly: pain, laceration, swelling, abrasion, bleeding, and fracture. Ambulances were dispatched as priority one (lights and siren) in 30, 196 (19%) cases; 84, 642 (54%) priority two, and 42, 156 (27%) as priority three. Following assessment and treatment, 123, 754 (79%) patients were transported to hospital, 32, 101 (20%) were not transported and <1% did not have transport data. Patients were transported at the following urgency: 2, 006 (1%) were transported via urgency one (lights and siren); 23, 365 (15%) via urgency two; 78, 584 (50%) via urgency three; and 19, 799 (13%) via urgency four to six. Conclusion: An increasing number of ambulance attendances are required each year for adults who fall. Between 2015–2020, approximately one-fifth of ambulances were dispatched to falls patients as a priority one, while after treatment only 1% patients were transported to hospital via the highest urgency. Learning Outcomes: Patient falls represent increasing demand for ambulance services.